Mechanical behavior study of microdevice and nanomaterials by Raman spectroscopy： a review - Qiu, Wei; Kang, Yi-Lan (Chinese science bulletin, 2014)
With the rapid development of micro/nano manufacturing technology and nanomaterials, the accurate measurement of the mechanical properties and behaviors at the micro-nano scale represents a new field of mechanical experiments. Raman spectroscopy, which is based on lattice dynamics theory, is applicable to the detection of the statistical information of the lattice structure deformation within the measuring points. Due to its peculiarities, such as non-destructiveness, convenience and high-resolution, this technology allows the on-line in situ measurement of residual stress in microstructures caused by processing and can also achieve the real-time deformation of graphene, carbon nanotubes and other nanomaterials under force loading. In recent years, mechanical measurements based on Raman spectroscopy technology have developed rapidly. In this review, Raman-based stress measurement theories for several commonly used materials are briefly described. Applications related to the residual stress measurements of microstructure and experimental investigations of the mechanical properties of low-dimensional nanomaterials are then reviewed. Finally, the development trend of this method is proposed.